Medical Ethics and Law : A curriculum for the 21st century - Dominic, Wilkinson; Herring, Jonathan; Savulescu, Julian (Elsevier, 2020)
This short textbook of ethics and law is aimed at doctors in training and in practice. Medical ethics and law are now firmly embedded in the curricula of medical schools. The ability to make clinical decisions on the basis of critical reasoning is a skill that is rightly presumed as necessary in today's doctors. Medical decisions involve not only scientific understanding but also ethical values and legal analysis. The belief that it is ethically right to act in one way rather than another should be based on good reasons: it is not enough to follow what doctors have always done, nor what experienced doctors now do. The third edition has been revised and updated to reflect changes in the core curriculum for students, developments in the law as well as advances in medicine and technology. It includes a new ‘extensions’ section, providing an outline of important developing areas in medical ethics.